From knowledge to profit: business reputation as a mediator in the impact of green intellectual capital on business performance - Anser, Muhammad Khalid; Naeem, Muhammad; Ali, Shoukat; Huizhen, Wang; Farooq, Sumair (Journal of intellectual capital, 2024)
PurposeThe purpose of this research is to support the green movement and improve corporate performance by focusing on green intellectual capital and its various components (e.g. green human capital, green structural capital and green relational capital). Furthermore, this study looks into the impact of business reputation in mediating the link between green intellectual capital qualities and business performance.Design/methodology/approachTo obtain data from the target population, this study employed quantitative techniques and a survey approach for data collection from respondents (managers and employees) of firms. The final sample size was 255.FindingsAccording to structural equation modeling green human capital, green structural capital and green relational capital all have a positive and statistically significant impact on organizational performance. Furthermore, the study shows that a company’s reputation plays an important role in mediating the relationship between the green intellectual capital component and business performance. These findings are confirmed by the natural resource-based perspective theory. This shows that developing green intellectual capital and promoting a green environment increases a company’s reputation among stakeholders, which promotes organizational performance.Research limitations/implicationsThe study’s findings will help policymakers and administrators better understand the role of green intellectual capital in business reputation and performance. Based on empirical data, the study would contribute to the management, environmental science and performance literature.Originality/valueTo the best of the researcher's knowledge, this is the first study to apply the natural resource-based view theory and to consider corporate reputation as a mediator between green intellectual capital and business success.